ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENAWARAN DAN PERMINTAAN SERAT KAPAS DI INDONESIA - Iwan Hermawan; Lukman Adam (Jurnal Ekonomi & Kebijakan Publik, 2010)
Cotton has strategic advantages among the other fibers and has big opportunity to develop in Indonesia’s arable land, through both intensification and extensification. This point of view takes its place when we realize that Indonesia is still depending on imported cotton to fill the domestic demand and it would threat national foreign exchange. The objectives of the study are to analyze factors affecting cotton supply and demand in Indonesia. The results of the study showed that factors of supply are influenced by production, import, and export. Cotton production is influenced by planting area of cotton and lag of cotton production. Cotton export is influenced by world cotton price, exchange rate, and lag of cotton export. Cotton import is influenced by population and lag of cotton import. Otherwise, cotton demand is influenced by population and lag of cotton demand. Generally, population is one of the important factors in cotton development as people badly need clothes to live normally.